Optimization of electromagnetic shielding and mechanical properties of reduced graphene oxide/polyurethane composite foam - Oraby, Hussein; Naeem, Ibrahim; Darwish, Mohammad; Senna, Magdy H.; Tantawy, Hesham Ramzy (Polymer engineering and science, 2022)
Reduced graphene oxide (RGO) is an effective polymer filler for shielding against electromagnetic interference (EMI). Its shielding efficiency rises as its concentration in polymer matrices increases. However, higher filler loading impedes polymer foaming and deteriorates the mechanical properties of the resulting foam. The goal of this work is to determine the optimal RGO concentration that can be loaded into polyurethane (PU) matrix to produce a composite foam with a high level of electromagnetic shielding along with good mechanical properties. To that end, different PU foam samples containing varying amounts of RGO were synthesized. The synthesized samples were characterized by scanning electron microscope (SEM), thermogravimetric analysis (TGA), Fourier transform infra‐red (FT/IR) and universal testing machine. Furthermore, the shielding efficiency of the samples was measured using a vector network analyzer over the frequency range of 8–12 GHz. The results revealed that the increase in RGO concentration enhances the mechanical and thermal properties of the prepared composite foam materials. The shielding effectiveness reached −23 dB at 5 wt% RGO concentration. The polyurethane‐RGO composite foam materials have been identified as potentially viable materials for use in electromagnetic shielding applications. Reduced graphene oxide (RGO) is an effective polymer filler for shielding against electromagnetic interference (EMI). The increase in RGO concentration enhances the mechanical and thermal properties of the prepared composite foam materials. The shielding effectiveness reached −23 dB at 5 wt% RGO concentration.